1988
DOI: 10.1007/bf00124009
|View full text |Cite
|
Sign up to set email alerts
|

Boundary-layer resistances of artificial leaves in turbulent air II: Leaves inclined to the mean flow

Abstract: The effect of turbulence on boundary-layer resistances to heat and water vapour transfer from leaves inclined to the mean airflow has.been studied using heated square plates in a wind tunnel. Heat and water vapour transfer coefficients increased with streamwise turbulence intensity for all angles of inclination of the plates to the mean flow, and the increase was dependent on the ratio of the longitudinal integral length scale to the plate dimension. This dependence on the turbulence length scale probably resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…in such cases. On the downstream (wake) side of an inclined plate, maximum enhancement was P K 2-\S at L^JL of 0'5 and 0'9 for inclination angles of 20° and 90°, respectively (Chen, Ibbetson & Milford, 19886). This clearly suggests a resonance effect between wake flow and free stream turbulence, reminiscent of the observations of van der Hegge Zijnen (1958).…”
Section: Effects Of Frequency and Scalesupporting
confidence: 59%
See 2 more Smart Citations
“…in such cases. On the downstream (wake) side of an inclined plate, maximum enhancement was P K 2-\S at L^JL of 0'5 and 0'9 for inclination angles of 20° and 90°, respectively (Chen, Ibbetson & Milford, 19886). This clearly suggests a resonance effect between wake flow and free stream turbulence, reminiscent of the observations of van der Hegge Zijnen (1958).…”
Section: Effects Of Frequency and Scalesupporting
confidence: 59%
“…Effects of serration near the leading edge increased transfer on square plates by up to factors of 1-4 at low angles of attack, broadening the range of angles 0 over which significant transfer enhancement is observed (Chen et al, 19886;section V.2a).…”
Section: {A) Lobes and Serrationmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, increased surface roughness can lead to increased heat exchange across surfaces of leaves (Chen et al, 1988) due to increased turbulence. Others have reported that changes in boundary layer characteristics can alter the response of plants to ambient CO concentrations (Aphalo & Jarvis, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…This report presents results from experiments with the plate held parallel to the mean flow: a second paper (Chen et al, 1988, hereafter referred to as II) presents the results from inclined plates.…”
Section: Introductionmentioning
confidence: 99%